Cross-Sectional Associations Between Lifetime Use of Psychedelic Drugs and Psychometric Measures During the COVID-19 Confinement: A Transcultural Study - Révész, Dóra; Ona, Genís; Rossi, Giordano N.; Rocha, Juliana M.; dos Santos, Rafael G.; Hallak, Jaime E. C.; Alcázar-Córcoles, Miguel Á.; Bouso, José C. (Frontiers in Psychiatry, 2021)
Background – One of the main public health strategies adopted at the beginning of the COVID-19 pandemic consisted of implementing strict lockdowns to stop the transmission of the virus. Despite being an effective measure, the confinement and the associated social isolation create a stressful, potentially lengthy situations that has been proven to have several psychological consequences. Given the potential benefits that certain psychedelic drugs have shown for the treatment of psychological disorders, this study aimed to assess the impact of lifetime psychedelic drug use on mental health in relation to the first strict lockdown adopted by various countries (April-July 2020). Methods – Subjects completed an online suvey that inquired about sociodemographic factors, activities, and lifestyle factors during confinement, as well as health and mental health related factors. Subjects were asked about their lifetime use of psychedelic drugs (MDMA, ayahuasca, psilocybin-containing mushrooms, LSD, peyote, San Pedro, Bufo alvarius or 5-MeO-DMT, and others), being classified as regular users (more than once per six months), occasional users, or non-users. The survey included psychometric tests used to assess psychological distress, peritraumatic stress, social support, coping mechanisms, psychopathological symptoms, and personality. Linear regressions were performed with psychedelic drug users as the independent variable and psychometric factors as the outcomes, while correcting for age, gender, language, religion, spirituality, and use of non-psychedelic drugs. Results – The study included 2,974 English, Portuguese, and Spanish speakers. On average, respondents were 36 years old and 70% were female. Psychedelic drug use, especially when used regularly, was associated with less psychological distress, less peritraumatic stress, and more social support. Regarding personality measures, psychedelic drug users scored higher on the novelty-seeking and self-transcendence scales, and lower on cooperativeness. Conclusion – Our findings showed that regular users of psychedelic drugs had less psychological stress and some personality differences when compared to occasional users and non-users. This suggests that either the use of psychedelics might be a protective factor itself or people with certain previous traits are more prone to frequently using psychedelic drugs. Future prospective longitudinal research should investigate the underlying processes observed in this study to develop consistent hypotheses.